Looking beyond relative age to understand relative advantage and disadvantage in talent development - Sweeney, Liam; de la Rubia, Alfonso; Taylor, Jamie; Bjørndal, Christian Thue (Frontiers in Sports and Active Living, 2024)
In this perspective article, we argue for a broader consideration of relative advantages and disadvantages in youth sport; a lens that considers the complex biopsychosocial factors that influence athlete development beyond relative age. We begin with a brief overview of Relative Age Effects (RAEs), with a particular focus on the proposed underlying mechanisms, followed by a discussion of the cultural and organisational considerations and implications that talent systems must consider when implementing interventions to counteract RAEs. We conclude by proposing key directions for future research in respect to RAEs and talent development more broadly. We argue that there is a need to consider the highly complex nature of RAEs, but also that there are no clear solutions to the issue of RAEs in youth sports, and that proposed solutions may come with unintended consequences. This should encourage us to experiment more, not less, with diverse ways of providing meaningful sports experiences that promote learning, psychosocial development, and performance. We suggest an urgent need for greater practical and research focus on supporting coaches, as they have the greatest capacity to understand the needs of individual athletes. In addition, systemically working towards equal access to skilful coaches. We encourage a shift in focus beyond descriptive methodologies of RAEs toward transformative research methodologies that include action-based research, complex interventions that incorporate context-sensitive qualitative methods, and other participatory research approaches.